2022
DOI: 10.1152/jn.00382.2021
|View full text |Cite
|
Sign up to set email alerts
|

The role of friction on skin wetness perception during dynamic interactions between the human index finger pad and materials of varying moisture content

Abstract: Mechanosensory inputs arising from dynamic interactions between the skin and moisture, such as when sliding a finger over a wet substrate, contribute to the perception of skin wetness. Yet, the exact relationship between the mechanical properties of a wet substrate, such as friction, and the resulting wetness perception, remains to be established under naturalistic haptic interactions. We modelled the relationship between mechanical and thermal properties of substrates varying in moisture levels (0.49x10-4; 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
(75 reference statements)
0
5
0
Order By: Relevance
“…One possibility might be that they relied more strongly than the other participants on the multisensory integration of mechanical cues (when combined with thermal cues) to detect wetness. [ 10,14 ] We have recently observed a similar phenomenon when comparing wetness perception between younger and older adults, whereby the latter group presented reduced wetness sensitivity in the presence of intact thermal sensitivity. [ 15 ] We hypothesized that age‐induced changes in tactile sensitivity might underlie differences in wetness perception in the absence of a thermal effect, a mechanism that could also underlie the outcomes observed in the nonresponders of the current study.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…One possibility might be that they relied more strongly than the other participants on the multisensory integration of mechanical cues (when combined with thermal cues) to detect wetness. [ 10,14 ] We have recently observed a similar phenomenon when comparing wetness perception between younger and older adults, whereby the latter group presented reduced wetness sensitivity in the presence of intact thermal sensitivity. [ 15 ] We hypothesized that age‐induced changes in tactile sensitivity might underlie differences in wetness perception in the absence of a thermal effect, a mechanism that could also underlie the outcomes observed in the nonresponders of the current study.…”
Section: Discussionmentioning
confidence: 70%
“…[ 9 ] In fact, mechanical parameters, such as friction, have been shown to play a secondary role in wetness perception when compared to the principal contribution of thermal factors. [ 10 ] Building on this observation, it has been demonstrated that touching a cold, dry object can generate a wetness illusion. [ 7,9 ] Our goal is to use this illusory perception to mediate wetness sensation from the prosthetic hand to an intact part of the body (e.g., the upper arm).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The participant was required to maintain a stable 5N normal force during the pulling action, using visual feedback from the digital meter described above. Normal and tangential forces were used to calculate the coefficient of kinetic friction (CoF) [14] and were averaged every 0.33s during each sliding movement. The data was analysed for the independent and interactive effects of plate temperature (3 levels: 24, 16, or 38ºC) and time (10 levels: 0 to 0.33s) by means of a 2-way repeated measure ANOVA.…”
Section: Skin Friction Experimentsmentioning
confidence: 99%
“…When considering contact between the skin and soft materials, which exhibit varying thickness and roughness, parameters such as stickiness and softness play a more significant role. 8,9 In particular, an increase in the softness of dry cloth has been shown to intensify wetness perception. 10,11 Nevertheless, these studies have been limited to static contact and have not explored the influence of surface properties of the soft material.…”
mentioning
confidence: 99%